1989
DOI: 10.1037/0278-6133.8.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Social support and recovery from surgery.

Abstract: This study examined the relationship of naturally occurring social support from the spouse with the preoperative anxiety and postoperative recovery of 56 male coronary-bypass patients. Patients were divided into groups based on whether the overall quality of their marital relationship was perceived to be relatively good or bad at the time of surgery and on whether they received relatively high or low spouse support in the hospital (defined in terms of frequency of visits). A fifth group (n = 16), consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
2
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(131 citation statements)
references
References 40 publications
3
120
2
6
Order By: Relevance
“…Kulik & Mahler [19] found that social support was significantly linked with health-related out-comes. Better social network help individuals to develop more sense of control which lead them to use more adaptive coping.…”
Section: Discussionmentioning
confidence: 99%
“…Kulik & Mahler [19] found that social support was significantly linked with health-related out-comes. Better social network help individuals to develop more sense of control which lead them to use more adaptive coping.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, factors that decrease social pain, such as social support, also decrease physical pain. Individuals who have more social support tend to experience less pain (Kulik & Mahler 1989, Zaza & Baine 2002, and viewing a picture or holding 606 Eisenberger the hand of a loved one reduces self-reported pain and pain-related neural activity (dACC, AI) to experimental pain stimuli (Eisenberger et al 2011b, Master et al 2009, Younger et al 2010. Additionally, factors that alter physical pain have similar effects on social pain.…”
Section: Consequences Of An Overlapmentioning
confidence: 99%
“…66,67 In addition, CRET programs have aspects of "group therapy," that is often used by psychologists and psychiatrists that may promote socialization and bonding with other patients in CRET who are at various stages in their recovery process. 66,68 Despite the significant improvements in PS following CRET, many patients continue to experience PS following CRET and have high morbidity and mortality. Further therapy directed at PS, including behavior modification, psychotherapy, and/or pharmacologic intervention could be required.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%